2017
DOI: 10.1007/s10236-017-1109-5
|View full text |Cite|
|
Sign up to set email alerts
|

Current and turbulence measurements at the FINO1 offshore wind energy site: analysis using 5-beam ADCPs

Abstract: We report concurrent measurements of ocean currents and turbulence at two sites in the North Sea, one site at upwind of the FINO1 platform and the other 200-m downwind of the Alpha Ventus wind farm. At each site, mean currents, Reynolds stresses, turbulence intensity and production of turbulent kinetic energy are obtained from two bottom-mounted 5-beam Nortek Signature1000s, high-frequency Doppler current profiler, at a water depth of approximately 30 m. Measurements from the two sites are compared to statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…these effects remains unknown but could range from localized within individual farms to broader spatial scales (Carpenter et al, 2016;Bakhoday-Paskyabi et al, 2018). The implications of these effects for fisheries production and commercial fisheries economics could be significant; hence, we suggest that the effect of wind farms on oceanographic variables be considered in environmental impact analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…these effects remains unknown but could range from localized within individual farms to broader spatial scales (Carpenter et al, 2016;Bakhoday-Paskyabi et al, 2018). The implications of these effects for fisheries production and commercial fisheries economics could be significant; hence, we suggest that the effect of wind farms on oceanographic variables be considered in environmental impact analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Primary and secondary production form the base of the marine food web and are associated with fisheries yields (Friedland et al, 2012;Stock et al, 2017). Both physical and biological oceanographic variables are likely to be affected by the operation of offshore wind farms (Floeter et al, 2017;Bakhoday-Paskyabi et al, 2018). However, few studies have directly demonstrated linkages between physical and biological oceanographic variables at these facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the ongoing atmospheric and oceanic measurements at Forschungsplattformen in Nord-und Ostsee (FINO) 1, 2, and 3 platforms have been widely analyzed by researchers (Bakhoday-Paskyabi et al 2018;Muñoz-Esparza et al 2012;Fischer 2006;Senet et al 2012;Li and Lehner 2013;Hallgren et al 2020;Sjöberg et al 2015;Tangvald 2012). Their meteorological records for over a decade in northern Europe support climatological studies on offshore wind energy applications.…”
Section: Measurement Data For Model Validationmentioning
confidence: 99%
“…In recent years, due to the installation of offshore windfarms in deeper waters, as well as the increase of wind turbine's power, other structures like jacket and tripods have been used, i.e., in Alpha Ventus offshore windfarm [17][18][19].…”
Section: Introductionmentioning
confidence: 99%